Level of Knowledge and Dengue Hemorrhagic Fever (DHF) Prevention Among Community Health Cadres and PKK Mothers in Cermen Village - Endah Budi Permana Putri; Firman Yudianto; Ana Lailatul Fitriya; Moh. Syafirul Nur Shafly (UNUSA Press, 2024)
Dengue Hemorrhagic Fever (DHF) is an acute disease that can lead to death. Mortality cases caused by this disease are still reported in Indonesia, indicating that DHF remains a significant public health concern that requires continuous vigilance and prevention efforts. The flagship community service program conducted by the Community Service Program (KKN) group aimed to improve community knowledge regarding the causes, prevention, and management of DHF. The methods employed included lectures and discussions. The lecture session covered the theoretical aspects of DHF, including its etiology, modes of transmission, prevention strategies, and management. This was followed by a demonstration on how to construct a mosquito trap, which was subsequently practiced directly by community health cadres and PKK mothers. The effectiveness of the program was evaluated using a pretest–posttest design. The results demonstrated an increase in participants’ knowledge regarding DHF and its prevention, with the average pretest score of 85 improving to an average posttest score of 100.